2004
DOI: 10.1515/dema-2004-0303
|View full text |Cite
|
Sign up to set email alerts
|

On Jordan Ideals and Jordan Derivations of Prime Rings

Abstract: Abstract. Let R be a 2-torsion free prime ring, and let J be a nonzero Jordan ideal and a subring of R. In the present paper it is shown that if d is an additive mapping of IntroductionThroughout this paper R will denote an associative ring with center Z(R). Recall that R is prime if aRb -(0) implies that a = 0 or b = 0. As usual [x, y] and x o y will denote the commutator xy -yx and anticommutator xy + yx, respectively. A ring R is said to be 2-torsion free, if whenever 2x = 0, with x G R, then x = 0. An addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…A well-known result due to Herstein (2002) states that every Jordan derivation on a prime ring of characteristic different from two is a derivation. This result was further generalized by many authors in various directions (see Ashraf et al 2001; Bres̆ar and Vukman 1991where further references can be found). Motivated by these results Ferrero and Haetinger (2002) generalized Herstein’s theorem for higher derivations and proved that every Jordan higher derivation on a prime ring of characteristic different from two is a higher derivation.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…A well-known result due to Herstein (2002) states that every Jordan derivation on a prime ring of characteristic different from two is a derivation. This result was further generalized by many authors in various directions (see Ashraf et al 2001; Bres̆ar and Vukman 1991where further references can be found). Motivated by these results Ferrero and Haetinger (2002) generalized Herstein’s theorem for higher derivations and proved that every Jordan higher derivation on a prime ring of characteristic different from two is a higher derivation.…”
Section: Introductionsupporting
confidence: 55%
“…We’ll proceed by induction on n . For n = 1, every generalized Jordan ( σ , τ )-higher derivation reduces to generalized Jordan ( σ , τ )-derivation and hence using Lemma 2.2( iii ) of (Ashraf et al 2001), we have …”
Section: Resultsmentioning
confidence: 98%
“…A famous result due to Bre²ar [5,Theorem 4.3], asserts that a Jordan triple derivation on a 2-torsion free semiprime ring is a derivation. Following the same line, a number of results have been obtained by several authors (see [2], [3], [4], [9], [18], [19], [22], [23]), where further references can be found.…”
Section: Introductionmentioning
confidence: 94%
“…Following B. Hvala [ [9], page 1447], an additive mapping F : R → R is called a generalized derivation if there exists a derivation d: R → R such that F (xy) = F (x)y + xd(y) holds for all x, y ∈ R. We call an additive mapping F : R → R a generalized Jordan derivation if there exists a derivation d: R → R such that F (x 2 ) = F (x)x + xd(x) holds for all x ∈ R [ [5], page 7]. In [ [5], Theorem], M. Ashraf and N. Rehman showed that in a 2-torsion-free ring R which has a commutator nonzero divisor, every generalized Jordan derivation on R is a generalized derivation.…”
Section: Introductionmentioning
confidence: 99%